Attitude of Female Students Towards Physical Education and Sports - Adhikari, Pashupati (Journal of Balkumari College, 2020)
This study presents an attitude of female students studying B.Ed. third year towards physical education and sports within Kathmandu valley. Initially, it was hypothesized that there is no significance difference in attitude of physical education and sports among female students of different campuses. From these 6 campuses, 184 female students were randomly selected. A five-point Likert-type scale was applied for data collection from the selected students who studied in B.Ed. third year. Altogether five opinion statements were used for data collection. It was found that all respondents showed positive attitudes towards physical education and sports. In order to test whether there is significant interdependence in score among the respondents in different perspectives. The chi-square test score was applied as statistical test at the 0.05 level of significance. The chi-test under contingency table: independent of opinion among the respondent, if (χ2>α=0.05 in different degree of freedom) and independent if (χ2≤ α=0.05 in different degree of freedom). For the measurement of attitude for physical education and sports,it has enough evidence in the data to accept alternatives hypothesis; there is relation or interdependence of attitude towards physical education and sports among the respondents. Because, the score is very high among the response of respondent. The study suggests that the university teacher must be accountable to construct professional environment.